ARCHAIC AND CLASSICAL BRONZE VESSELS FROM THE IRON AGE CEMETERY OF BOROVA (ALBANIA): A COMMUNITY IN TRANSITION - Sabina Veseli (Journal of Ancient History and Archaeology, 2020)
The cemetery of Borova is situated in the region of Kolonja in south-east Albania. The cemetery had around 49 graves which contained rich inventories of pottery, jewelry , weapons, etc. The artifacts date the cemetery mainly in the late Iron Age, i.e., around 6th-5th centuries BC, and attest to intensive exchange of a part of the local productions with northern Greece. The typology of the tombs is closely associated to the princely graves of the Balkans as attested by the richness of the inventory. The discovery of a bronze olpe, two phiales and a bronze cylix demonstrates the presence of Greek Archaic and classical imports of bronze vases in the Illyrian territory. The geographical vicinity enabled an active trade in the region, probably between the pastoral societies which did not trade very valuable goods, as was the case of the tombs of Trebenishte and Novi Pazar, but more modest finds in bronze. These artifacts indicate an Iron Age society in transition to the Archaic and classical period, with the use of valuable bronze vases by the Illyrian chiefs as the first signs of their ‘Hellenization’. Keywords: bronze vessels, funerary, Iron Age, archaic period, Illyria.